2023
DOI: 10.1002/smtd.202201440
|View full text |Cite
|
Sign up to set email alerts
|

Anion Storage of MXenes

Abstract: Recently, anion storage materials have gained significant attention owing to the widened cell voltage and additional anion storing capacity for a large energy density. MXenes are considered as the emerging anion storing materials owing to their sufficient interlayer spacing, rich surface chemistries, tunable structures, remarkable electrochemical properties, and mechanical integrity. Herein, a comprehensive review on the anion storage of MXenes covering their anion storage mechanism and state‐of‐the‐art chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…The Lin et al study 54 also demonstrates that MXene layers can intercalate TFSI − anions due to the electrostatic attraction under positive polarization in an EMI-TFSI ionic liquid electrolyte. Wang et al 55 concluded that the accommodation of positively charged components (e.g., metal cations and positively charged g-C 3 N 4 ) into MXene-based materials is a viable approach to avoid the electrostatic repulsion between anions and MXenes, thus endowing MXenes with excellent [AlCl 4 ] − trapping capability for Al-ion batteries.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The Lin et al study 54 also demonstrates that MXene layers can intercalate TFSI − anions due to the electrostatic attraction under positive polarization in an EMI-TFSI ionic liquid electrolyte. Wang et al 55 concluded that the accommodation of positively charged components (e.g., metal cations and positively charged g-C 3 N 4 ) into MXene-based materials is a viable approach to avoid the electrostatic repulsion between anions and MXenes, thus endowing MXenes with excellent [AlCl 4 ] − trapping capability for Al-ion batteries.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A high-potential triphenylphosphine selenide organic cathode (TP-Se) was reported as the cathode of DIBs [181], and (TP-Se) − to (TP-Se) 0 to (TP-Se) + conversion could be used to store anions. MOF [182], and MXenes [183] were reported as dual-ion hosts.…”
Section: Conversion-type Cathodesmentioning
confidence: 99%
“…), and periodically arrayed interlayers. [38,40] The fabrication diagram of the I 2 /MXene cathode is shown in Figure 3e. They demonstrate that there are three possible iodine/polyiodide species adsorption sites (Nb, C, and T x (O), Figure 3f − on Nb site and density of states (DOS) patterns near the Fermi energy (E f ) around Nb site further verify the strong interaction between iodine/polyiodide species and Nb 2 CT x host.…”
Section: Advanced Cathode Framework Constructionmentioning
confidence: 99%